Extending the family of heteroditopic calix[4]diquinone receptors for cooperative AND ion-pair recognition - McConnell, A; Serpell, C; Beer, P (2012)
New heteroditopic calix[4]diquinone receptors with different anion binding units and calix[4]diquinone scaffolds have been synthesised. Ion-pair binding studies using UV/visible and 1H NMR spectroscopies reveal that receptors 1, 2 and 4 are cooperative AND ion-pair receptors, which display little affinity for 'free' ions but enhanced binding of the ion-pairs NaCl, NH 4Cl and KCl. The more preorganised receptor 2 binds the ion-pairs more weakly than receptor 1. Varying the nature of the calix[4]diquinone scaffold appears to have little effect on ion-pair binding, although the calix[4]diquinone framework is more conformationally flexible than the tert-butylcalix[4]diquinone one and can be synthesised using the milder oxidant chlorine dioxide. This journal is © The Royal Society of Chemistry and the Centre National de la Recherche Scientifique.